Energy benefit of a cascade liquid desiccant dehumidification in a desiccant and evaporative cooling-assisted building air-conditioning system. (25th January 2019) - Park, Joon-Young; Dong, Hye-Won; Cho, Hye-Jin; Jeong, Jae-Weon
Highlights: The energy benefit of two-stage (or cascade) liquid desiccant approach over the single-stage case was investigated. The two-stage liquid desiccant case showed enhanced dehumidification performance and better controllability. The cascade approach showed 17.4% lower primary energy consumption than the single-stage case. The overall thermal and primary coefficients of performance were enhanced by 41% and 20%, respectively. Abstract: The main objective of this study was to estimate the impact of dehumidification with a cascade liquid desiccant on the primary energy consumption in a liquid desiccant and evaporative cooling-assisted 100% outdoor air system. Detailed energy simulations were performed for two systems serving an identical office space: the conventional liquid desiccant and indirect/direct evaporative cooling-assisted 100% outdoor air system (LD-IDECOAS) (i.e., Case 1) having a single-stage liquid desiccant dehumidification section, and a retrofit case of the LD-IDECOAS having a cascade liquid desiccant section (i.e., Case 2) consisting of a two-stage liquid desiccant dehumidifier. The results showed that Case 2 consumed 12% less primary energy under the peak load condition and 17.4% less primary energy during the cooling season. The overall thermal and primary coefficients of performance of Case 2 were 0.78 and 2.05, respectively, whereas those of Case 1 were 0.65 and 1.45, respectively. In addition, it was also observed that Case 2 could provide lower supply air temperature to the conditioned space compared with Case 1 owing to enhanced evaporative cooling performance, which was mainly caused by enhanced dehumidification in the cascade liquid desiccant section. The lower supply air temperature resulted in reductions in fan and pump energy consumptions during the operation.